Botulinum toxin type A and cervical dystonia: a seven-year follow-up - Carlos Henrique F. Camargo; Hélio Afonso G. Teive; Nilson Becker; Renato P. Munhoz; Lineu César Werneck (Arquivos de Neuro-Psiquiatria)
Most cases of cervical dystonia (CD) are idiopathic, and focal injections of botulinum toxin A (BoNT/A) are the treatment of choice. The objective of our study was to document the effects of long-term BoNT/A treatment in idiopathic CD patients. Fifty-eight patients with idiopathic CD were recruited from March 2001 to May 2002. Twenty-eight of the subjects were available for reassessment after seven years. During this period, all had received regular treatment with BoNT/A injections. Clinical information about patients and the severity of CD (TWSTRS and VAPS) at baseline assessment (2001-2002) and follow-up (2008-2009) was compared. Significant motor improvement was detected based on TWSTRS scale scores, which were used to analyze clinical severity (19.6±6.6 and 17.7±4.8; p<0.05). There was no improvement in the severity of cervical pain (p=0.43). In conclusion, BoNT/A was a safe and effective long-term therapy for CD.